﻿Plutarco e la cultura figurativa nell’età di Paolo iii : Castel Sant’Angelo, Sala Paolina - Guerrini, Roberto (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1985)
The significance of Plutarch as the major historical source for the iconographical scheme of the decoration in the Sala Paolina, Castel Sant’Angelo (1540s) is discussed. Consideration of the fresco cycle in the room is comprehensively focused on the allusions in the iconographic programme to Paul iii and the ideology of his pontificate. The full range of literary sources is investigated and the primacy of Plutarch shown through detailed reading of each scene on the ceiling and walls. The clear associations between Alexander and Paul iii are also noted. From this, observations are made regarding the programmatic intentions of the cycle as a visualization of the political and cultural aims of Paul iii.